PENYULUHAN ASPEK REPRODUKSI DAN PELAYANAN KESEHATAN HEWAN DALAM RANGKA MENYUKSESKAN ANJING KINTAMANI SEBAGAI RAS DUNIA - Gunawan, I.W.N.F.; Jayanti, P.D.; Dharmayudha, A.A.G.O.; Kardena, I.M.; Monica, W.O.S.; Puja, I.K. (Buletin Udayana Mengabdi; Vol 24 No 2 (2025): Buletin Udayana Mengabdi, 2024)
This community service activity aims to reduce health problems in Kintamani dogs in Sukawana village, Kintamani District, Bangli Regency, namely worms, and maintenance management. The methods used in this community service are in the form of counseling on aspects of reproduction and maintenance from house to house and carrying out Animal health services in the form of providing vitamins, deworming to healthy livestock and providing treatment to sick animals. It is hoped that through this service, sick Kintamani dogs will improve their health and reduce the incidence of disease, and improve the quality of Kintamani dogs so that in this case they will be able to increase maintenance income and at the same time make the Kintamani breed dog program recognized worldwide, in Sukawana Village, Kintamani District, Bangli Regency Keywords: Kintamani dog, reproduction, Sukawana Village